Interlanguage Analysis on Speech Produced by EFL Learners - Ni Luh Putu Sri Adnyani; Dewa Ayu Novi Kusumawardani (Magister of Linguistic, Postgraduated Program, Universitas Warmadewa, 2020)
Indonesian EFL Learners experience erroneous speech in the process of learning the target language. Interlanguage, the errors that contain linguistic features which neither belong to the first language (L1) nor the target language becomes the focus of this study. The study aims to analyze the native and target language influence on the interlanguage produced by the students in their speech production. This study was designed in qualitative research approach. The data was collected through interviewed of 20 eighth grade students in English using a guided interview technique that contains 15 questions. The oral responses produced by the students were recorded, identified, described, and explained. The results show that in the syntactic and lexicon levels, both native and target language influenced the students’ interlanguage production. Native language influence includes 1) the use of Indonesian syntactic pattern; 2) the use of Indonesian acronym; 3) the use of Indonesian words; 4) omission of –s in plural forms; 5) omission of to be; 6) subject deletion; and 7) the use of verbs. Target language influence is observed in overgeneralization of articles, the use of to be, and the overgeneralization of ending –ed in the past tense.